Kajian Keamanan Sistem Informasi Akademik Menggunakan Framework COBIT 5 - Supit, Yonal; Edy Irwansyah (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2024)
This study examines the security of academic information systems using the COBIT 5 Framework. Key issues are uncertainty in protecting student and staff data, the potential for cyberattack vulnerabilities, and non-compliance with international security standards. The goal is to evaluate the security level of the system and suggest improvement recommendations according to COBIT 5 principles. Research methods include Renstar IT policy analysis, system audits, and interviews with IT personnel and related academic communities. Data is analyzed quantitatively to identify weaknesses and opportunities for improvement. The COBIT 5 framework is used as a security assessment framework. The results highlight the need for improvement, including access management, activity monitoring, and continuous improvement plans. Using COBIT 5, substantial measures such as strengthening access controls and developing disaster recovery plans can be identified. The research emphasizes the importance of a structured approach in improving the security of academic information systems, with COBIT 5 as a useful tool. With the right measures, system security can be enhanced to protect the integrity, confidentiality, and availability of critical data for educational institutions. In conclusion, these measures demonstrate how important COBIT 5 implementation is in addressing information security challenges in academic environments.